Low-dose IL-2 improved clinical symptoms by restoring reduced regulatory T cells in patients with refractory rheumatoid arthritis: A randomized controlled trial - Wang, Jia; Zhang, Sheng-Xiao; Chang, Jia-Song; Cheng, Ting; Jiang, Xiao-Jing; Su, Qin-Yi; Zhang, Jia-Qi; Luo, Jing; Li, Xiao-Feng (Frontiers in Immunology, 2022)
Background Regulatory T cells (Tregs) have been found to play crucial roles in immune tolerance. However, the status of Tregs in refractory rheumatoid arthritis (RA) is still unclear. Moreover, low-dose interleukin-2 (IL-2) has been reported to selectively promote the expansion of Tregs. This study investigated the status of CD4+ Tregs and low-dose IL-2 therapy in patients with refractory RA. Methods The absolute number of CD4+CD25+FOXP3+ Treg (CD4 Treg), CD4+IL17+ T (Th17), and other subsets in peripheral blood (PB) from 41 patients with refractory RA and 40 healthy donors was characterized by flow cytometry combined with an internal microsphere counting standard. Twenty-six patients with refractory RA were treated with daily subcutaneous injections of 0.5 million IU of human IL-2 for five consecutive days. Then, its effects on CD4 Treg and Th17 cells in PB were analyzed. Results A decrease in the absolute number of PB CD4 Tregs rather than the increase in the number of Th17 was found to contribute to an imbalance between Th17 and CD4 Tregs in these patients, suggesting an essential role of CD4 Tregs in sustained high disease activity. Low-dose IL-2 selectively increased the number of CD4 Tregs and rebalanced the ratio of Th17 and CD4 Tregs, leading to increased clinical symptom remission without the observed side effects. Conclusions An absolute decrease of PB CD4 Tregs in patients with refractory RA was associated with continuing disease activation but not the increase of Th17 cells. Low-dose IL-2, a potential therapeutic candidate, restored decreased CD4 Tregs and promoted the rapid remission of patients with refractory RA without overtreatment and the observed side effects. Clinical trial registration http://www.chictr.org.cn/showproj.aspx?proj=13909, identifier ChiCTR-INR-16009546.